A NUMERICAL STUDY ON QUASI MONTE CARLO METHODS BASED ON RANDOMLY SHIFTED LATTICE RULE FOR COMPUTATION OF MULTIPLE INTEGRALS: A NUMERICAL STUDY ON QUASI MONTE CARLO METHODS BASED ON RANDOMLY SHIFTED LATTICE RULE FOR COMPUTATION OF MULTIPLE INTEGRALS - Todorov, Venelin; Dimitrov, Valentin; Tsvetkov, Iliyn (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
A comprehensive numerical study between randomly shifted lattice rules and Fibonacci based lattice rule for computing multidimensional integrals has been done. The methods have not been compared before and both are recommended in case of smooth integrands. The two stochastic methods are completely different thus it is not trivial of which one of them outperforms the other. We consider a case study with smooth integrand functions of different dimensions.